Massive Philanthropy as Marketing Competition in The New Normal Era During Pandemic - Muhammad Nizar; Muhammad Chabibi (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2021)
This paper explains the philanthropic phenomenon that occurred in Indonesian people, especially the people of Cirebon City when the transmission of the covid-19 virus reached it’s peak again in November 2020. Basically, the philanthropic movement in the Covid-19 pandemic era emerged based on chaotic humanitarian attention and the uncertain economic stability of the country. This provides a stimulus to philanthropic activists to participate in social-humanitarian concerns and social-economic restoration. This type of research is qualitative with interview methods and online media documentation. This study concludes that the philanthropic movement should be based on humanitarian solidarity and religious normativity. However, several philanthropic activists in Cirebon City have used the opportunity of the COVID-19 pandemic moment as a personal economic recovery by using accurate marketing management wrapped in social philanthropy. This is a new motive that combines the humanitarian philanthropy movement with a marketing work system when COVID-19 as a natural disaster strikes with the aim of helping people as well as marketing their commodity products. The reason is that the demands for economic improvement during a pandemic require philanthropic activists to give and share as well as sell and promote.